A Proposed Method for Solving Fuzzy System of Linear Equations - Reza Kargar; Tofigh Allahviranloo; Mohsen Rostami-Malkhalifeh; Gholam Reza Jahanshaloo (The Scientific World Journal)
This paper proposes a new method for solving fuzzy system of linear equations with crisp coefficients matrix and fuzzy or interval right hand side. Some conditions for the existence of a fuzzy or interval solution of m×n linear system are derived and also a practical algorithm is introduced in detail. The method is based on linear programming problem. Finally the applicability of the proposed method is illustrated by some numerical examples.